TFDP3 as E2F Unique Partner, Has Crucial Roles in Cancer Cells and Testis - Huang, Jiahao; Wang, Yini; Liu, Jinlong; Chu, Ming; Wang, Yuedan (Frontiers in Oncology, 2021)
Transcription factor DP family member 3 (TFDP3) is a cancer-testis antigen, mainly expressed in normal testis and multiple cancers. TFDP3 gene (Gene ID: 51270) is located on the chromosome X and shares a high degree of sequence homology with TFDP1 and TFDP2, which can form heterodimers with E2F family members and enhance DNA-binding activity of E2Fs. In contrast to TFDP1 and TFDP2, TFDP3 downregulates E2F-mediated transcriptional activation. During DNA damage response in cancer cells, TFDP3 is induced and can inhibit E2F1-mediated apoptosis. Moreover, TFDP3 is involved in cell autophagy and epithelial-mesenchymal transition. Regarding cancer therapy opportunity, the transduction of dendritic cells with recombinant adenovirus-encoding TFDP3 can activate autologous cytotoxic T lymphocytes to target hepatoma cells. Here, we review the characterization of TFDP3, with an emphasis on the biological function and molecular mechanism. A better understanding of TFDP3 will provide new insights into the pathological mechanisms and therapeutic strategies for cancers.